Newborn Skin Care is the Basis for Prevention of Atopic Dermatitis Development - Nikolay N. Murashkin; Leonid A. Opryatin; Roman V. Epishev; Alexander I. Materikin; Eduard T. Ambarchyan; Roman A. Ivanov; Dmitriy V. Fedorov; Daria S. Kukoleva (Вопросы современной педиатрии, 2021)
Healthy newborn skin care is challenging task. The basic principles of care should be taught to both medical staff and parents. This care is more crucial in children with atopic dermatitis who have abnormal skin acidity due to multifactorial exposure. Significant pH reduction leads to aggravation of the skin process that requires active therapeutic measures. The article presents guidelines for the first infant's skin cleaning, for conducting first and daily bathing, for using cleansing agents and daily care solutions to prevent skin acidity disorders and the development of atopic dermatitis.